Assessing protein - ligand binding modes, novel drug skeleton candidates for PDE4B and conformational rearrangements of EF-TU in GTP hydrolysis with computational tools - Çifci, Gülşah. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
In the first part of this dissertation, computer-aided drug design approaches, structurebased methodologies such as docking, molecular dynamics simulations and Gibbs free energy calculations with Molecular Mechanics-Generalized Born/Surface Area (MMGB/SA) and ligand-based drug design methodologies like pharmacophore modeling are used to propose novel inhibitors for Phosphodiesterase4B (PDE4B) inhibitors. Virtual screening based on structure-based pharmacophore models has been performed for PDE4B inhibitors. The free energy of binding (ΔGbinding) as the total average of 40 independent simulations of each PDE4B inhibitors has been calculated with the MM-GB/SA method. The linear correlation between half maximal inhibitory concentration (IC50) and MM-GB/SA results have been analyzed with the linear dependency between binding affinity (Ki) and IC50, assuming that Michaelis-Menten constant (Km), substrate concentrations [S], and experimental conditions are similar. In the second part of this dissertation, the role of important amino acids in GTPase activity of EF-Tu-GTP for different organisms (Thermos-Aquaticus (T.aquaticus) and Escheria Coli (E.coli) complex have been determined by the aid of molecular dynamics (MD) simulations. The study has been carried out by comparing the experimental results with the results of the MD simulations. The conformational changes during the GTP hydrolysis in the Elongation factor-thermo unstable (EF-Tu) is explained with MD simulations.
Keywords: Phosphodiesterases -- Inhibitors.; Phosphodiesterases -- Inhibitors -- Therapeutic use.; Amino acids.